The annual periodization of training volumes of international-level cross-country skiers and biathletes - Myakinchenko, E. B.; Kriuchkov, A. S.; Adodin, N. V.; Feofilaktov, V. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To compare the training-volume (TrV) distribution of Russian international-level male biathletes, female biathletes, and cross-country skiers (XC) during an annual cycle. Methods: Day-to-day TrVs were recorded and averaged for a 5-year period for male biathletes (n=6), female biathletes (n=8), and XC (n=14) with VO2max values of 77.7 (3.8), 64.6 (1.9), and 79.4 (3.5) mL/min.kg, respectively. Results: The volumes of low- and moderate-intensity endurance training and all types of nonspecific endurance and strength training gradually decreased toward the competition period. However, the volumes and proportions of high-intensity endurance training and specific exercises (roller skiing, skiing, and shooting during high-intensity endurance training) increased by the time of the competition period. The total volume of training, volumes of low- and moderate-intensity endurance training, moderate- and high-load strength training (70%-95% 1RM), and power/speed loads did not increase gradually but reached their maximum immediately after a short stage of initial training. All teams employed the "pyramid" model of intensity distribution. Compared with the biathletes, XC demonstrated a larger (P<.01) annual volume of endurance training (~190 h), low-intensity endurance training (~183 h), and strength training (~818 sets). They also engaged in more upper-body and core-strength exercises (~769 sets), and they reached their maximum aerobic TrVs in June, while the biathletes reached theirs in July. Conclusions: In recent decades, the traditional model of periodization has been altered. The Russian XC and biathletes had significant differences in TrVs.